2021
DOI: 10.32854/agrop.v14i6.1850
|View full text |Cite
|
Sign up to set email alerts
|

Lactation curve, milk production of Pelibuey ewes and preweaning growth rate of the lambs

Abstract: Objective: To estimate the lactation curve and milk production of Pelibuey ewes andthe relationship with preweaning growth rate of the lambs.Design/methodology/approach: Forty five Pelibuey ewes were milked during 70days in Montecillo, México, in 2018, to estimate daily and total milk production. Thelactation curve was fitted with the incomplete gamma function. In addition, the effectsof type of birth and ewe weight at milking on milk production were analyzed, andcorrelations were calculated between ewe milk p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The highest milk yield was observed during the second week of lactation in D'man ewes in this study (Figure 3). The same period of appearance of maximum production was recorded in the same breed in Morocco (Boujenane and Kerfal 1992 [14]), at Rembi ewes (Benchohra et al 2014b [20]), at the Sardi, Timahdite and Beni Guil breeds (Boujenane et al 1996 [12]), at the prolific Avichan breed (Prakash et al 2019 [15]) and in Pelibuey ewes (Rodríguez-Álvarez et al 2021 [21]). However, a peak in production was obtained in the third week of lactation in D'man ewes in Tunisia by Dhaoui et al (2018) [22] and in the prolific Priangan breed (Tiesnamurti et al 2012 [16]).…”
Section: Lactation Curvementioning
confidence: 61%
See 1 more Smart Citation
“…The highest milk yield was observed during the second week of lactation in D'man ewes in this study (Figure 3). The same period of appearance of maximum production was recorded in the same breed in Morocco (Boujenane and Kerfal 1992 [14]), at Rembi ewes (Benchohra et al 2014b [20]), at the Sardi, Timahdite and Beni Guil breeds (Boujenane et al 1996 [12]), at the prolific Avichan breed (Prakash et al 2019 [15]) and in Pelibuey ewes (Rodríguez-Álvarez et al 2021 [21]). However, a peak in production was obtained in the third week of lactation in D'man ewes in Tunisia by Dhaoui et al (2018) [22] and in the prolific Priangan breed (Tiesnamurti et al 2012 [16]).…”
Section: Lactation Curvementioning
confidence: 61%
“…Similarly, Prakash et al (2019) [15] for the prolific breeds Avishaan and GMM also reported similar performance in ewes for different weight categories. However, Ángeles Hernández et al (2018) [26] in the East Friesian breed, and Rodríguez-Álvarez et al (2021) [21] in the Pelibuey breed reported the effect of body weight of ewes at mating, in midgestation, at lambing and during lactation on the milk yield of ewes. The absence of the weight effect can be justified by the mobilization of the ewe's body reserves to ensure sufficient milk production for the lambs.…”
Section: Factors Of Variation In Milk Production Of D'man Ewesmentioning
confidence: 99%